Menelusuri Kendala Mahasiswa dalam Memahami Radiasi Benda Hitam Melalui Simulasi PHET - Dwi Sarmaulina Simamora; Miranda Sigalingging; Vincentius Rajamin Sirait (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to identify the difficulties faced by Physics Education students in understanding the concept of black body radiation and explore the potential of PhET simulations in overcoming these difficulties. The method of this research was to conduct interviews with five students from the physics education study program. It was found that the students had difficulty understanding the abstract concept of black body radiation, there was a lack of practical work, and limited lecturer support. PhET Simulation, an interactive software, is used to identify difficulties and is a tool to help overcome these difficulties. The results showed that the PhET simulation was effective in helping students visualize the concept of black body radiation and overcome difficulties in understanding. Students found this simulation interesting and helped them understand concepts such as the Stefan-Boltzmann law and the Wien shift. This research concludes that PhET simulations can be an effective tool in learning quantum physics, especially the concept of black body radiation. By providing interactive visualizations, this simulation can help students overcome difficulties in understanding abstract concepts and improve their overall understanding.